Recent results from the Upper Paleolithicsite of Poiana Cireşului - Piatra Neamţ (North-Eastern Romania) - Carciumaru, Marin; Anghelinu, Mircea; Steguweit, Leif; Lucas, Géraldine; Niţă, Loredana; Fontana, Laure; Brugère, Alexis; Hambach, Ulrich; Mărgărit, Monica; Dumitrașcu, Valentin; Cosac, Marian; Dumitru, Florin; et al. (New aspects of the Central and Eastern European Upper Palaeolithic - methods, chronology, technology and subsistence, 2010)
The Upper Paleolithic site of Poiana Cireșului is located in the Bistrița Valley in the Eastern Carpathian area of Northeastern Romania. The long geological sequence preserved at Poiana Cires¸ului is attributed to the last Würm Pleniglacial and to the Tardiglacial. To date, four Epigravettian and Gravettian layers have been excavated, and at least two more have been documented through recent core tests in the lower part of the deposits. The oldest excavated Gravettian layer has recently yielded a date of 26,000 BP, which suggests that the deposits at Poiana Cires¸ului very likely preserve the longest geological and cultural Upper Paleolithic sequence in the area. Given the excellent state of preservation and the rich archaeological record, the site of Poiana Cires¸ului offers an opportunity for better understanding the Upper Paleolithic cultural dynamics in Eastern Romania. Moreover, recent data casts serious doubts on the time-honored cultural framework developed in the 1950s by C. S. Nicolăescu-Plops¸or for the Upper Paleolithic of the Bistrița Valle